Situations contextuelles dans l'enseignement de physique au lycée - ABDELAZIZ EL MOUSSAOUY; AHMED ERRAHMANI; JAMILA ABDERBI (Metaichmio Publications, 2015)
This work undertakes the task of examining the role of the integration of history as well as the manipulation of contextual issues in the teaching of physics at the Moroccan Bachelor. The study is realised by analysing the corresponding physics textbooks. The approaches target anthropological theories of knowledge, semiotic registers and praxeological tasks. The results show that textbooks have a low contribution of contextual situations. We also noticed a very low presence of the history of science in physics textbooks. These results are likely to enlarge the field of research related to the teaching of physics, and a reference tool for the development of programs and curricula from the standpoint of effective learning.